2021
DOI: 10.1109/access.2021.3082177
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Co-Worker Support and Supervisor Support Among the Middle and Senior Management in the Manufacturing Industry

Abstract: The purpose of the this research work was to evaluate the impact of social support (through its two dimensions: co-worker support and supervisor support) on the reduction of the burnout syndrome (considering its three dimensions: emotional exhaustion, professional efficacy, and cynicism) from two proposed models that show clear differences. Social support was assessed using the Job Content Questionnaire instrument, and the burnout syndrome was measured through the Maslach Burnout Inventory -General Survey. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
2
3
0
1
Order By: Relevance
“…They also feel comfortable consulting their coworkers for tasks they doubt to reduce errors. These results are consistent with Macias-Velasquez et al (2021), who found the study results indicate that having social support in the company will help reduce burnout among employees in the industrial sector, thereby increasing employee satisfaction and productivity. It is worth mentioning that social support has the greatest influence on workers' feelings of emotional exhaustion.…”
Section: Coworker Support and Job Performancesupporting
confidence: 91%
“…They also feel comfortable consulting their coworkers for tasks they doubt to reduce errors. These results are consistent with Macias-Velasquez et al (2021), who found the study results indicate that having social support in the company will help reduce burnout among employees in the industrial sector, thereby increasing employee satisfaction and productivity. It is worth mentioning that social support has the greatest influence on workers' feelings of emotional exhaustion.…”
Section: Coworker Support and Job Performancesupporting
confidence: 91%
“…Taken together, these results are consistent with previous empirical research, showing that workload is positively associated with health impairment linked to work-related stress (see Nixon et al, 2011 for a review and meta-analysis). Similarly, our results are consistent with prior research showing that PSS (e.g., from colleagues or supervisors) is negatively associated with emotional exhaustion and psychophysical strain (Valadez-Torres et al, 2018;Macias-Velasquez et al, 2021; see also Viswesvaran et al 1999, for a meta-analysis).…”
Section: Discussionsupporting
confidence: 92%
“…Next, Previous research has shown that leadership style [ 98 ] and superior support [ 99 ] have a direct impact on burnout and are an important source of job resources, however, there has been limited exploration into how trust from superiors impacts employee burnout. Hailed as an important resource in the workplace [ 2 ], trust is a classic and challenging research topic.…”
Section: Discussionmentioning
confidence: 99%